2011
DOI: 10.1155/2012/506572
|View full text |Cite
|
Sign up to set email alerts
|

Control of the Morphology of Molybdenum Dioxide Nanoparticles

Abstract: Synthesis of MoO 2 nanoparticles with one-dimensional (1D) and spherical morphologies in aqueous solutions, through hydrothermal process was investigated. The materials were studied by x-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), Infrared spectroscopy (FTIR) and thermal analysis (TG). It was found that the quantity of organic compound influenced the size and shape of the final product. The possible formation mechanism of MoO 2 microspheres and nanowires w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…The characteristics vibrations due to Mo-O (Fig. 3c) stretching appear at 448 and 670 cm -1 with a relatively strong peak due to some double bond character (Mo=O) appearing at 962 cm -1 [27][28][29]. For MoN (Fig.…”
Section: Electrochemical Measurementsmentioning
confidence: 96%
See 1 more Smart Citation
“…The characteristics vibrations due to Mo-O (Fig. 3c) stretching appear at 448 and 670 cm -1 with a relatively strong peak due to some double bond character (Mo=O) appearing at 962 cm -1 [27][28][29]. For MoN (Fig.…”
Section: Electrochemical Measurementsmentioning
confidence: 96%
“…N-doping of CNT provided n-type carrier concentration along with reactive sites for interfaces and high conductivity for efficient synergistically integrated composite structure. When used as anode material, the strong bonding between MoN and carboxyl groups of N-CNT along with high surface area (369 m 2 g -1 ), small particle size(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) nm), high dispersion and mesoporosity (6nm average pore size) unite together to extend the electrochemical kinetics of LIBs.…”
mentioning
confidence: 99%
“…The FT‐ IR spectra of MoO 2 @C and MoO 3 @SiC catalysts are shown in Figure . In MoO 2 @C catalyst, the peaks at 612 and 920 cm −1 can be assigned to the Mo‐O‐Mo and Mo = O vibrations of MoO 2 nanoparticles in this catalyst, respectively . The existence of MoO 3 in MoO 3 @SiC catalyst was confirmed by the peaks at 578 and 906 cm −1 that are related to the vibration of Mo‐O‐Mo and Mo = O bonds in MoO 3.…”
Section: Resultsmentioning
confidence: 69%
“…In MoO 2 @C catalyst, the peaks at 612 and 920 cm −1 can be assigned to the Mo-O-Mo and Mo = O vibrations of MoO 2 nanoparticles in this catalyst, respectively. [37,38] Figure 3. The blue pattern shows the diffraction peaks of MoO 2 @C at 2θ = 26.1, 37.0, 41.7, 50.1, 50.8, 53.5, 60.7, 66.9, and 72.6°reflections that are attributed to the monoclinic MoO 2 (JCPDS: 86-0135).…”
Section: Characterizationmentioning
confidence: 99%
“…In this process, the weight of control sample was increased by approximately 9.5% as compared to its initial weight. Naouel et al reported that the weight gain by MoO 3 sample in TGA was due to its oxidation [20] Zhang et al reported that the theoretical weight gain during oxidation of MoO 2 to MoO 3 is 12.5% [21].…”
Section: Thermal Analysismentioning
confidence: 99%